Field-realistic antidepressant exposure disrupts group foraging dynamics in mosquitofish. (29th November 2019) - Martin, Jake M.; Saaristo, Minna; Tan, Hung; Bertram, Michael G.; Nagarajan-Radha, Venkatesh; Dowling, Damian K.; Wong, Bob B. M.
Abstract : Psychoactive pollutants, such as antidepressants, are increasingly detected in the environment. Mounting evidence suggests that such pollutants can disrupt the behaviour of non-target species. Despite this, few studies have considered how the response of exposed organisms might be mediated by social context. To redress this, we investigated the impacts of two environmentally realistic concentrations of a pervasive antidepressant pollutant, fluoxetine, on foraging behaviour in fish ( Gambusia holbrooki ), tested individually or in a group. Fluoxetine did not alter behaviour of solitary fish. However, in a group setting, fluoxetine exposure disrupted the frequency of aggressive interactions and food consumption, with observed effects being contingent on both the mean weight of group members and the level of within-group variation in weight. Our results suggest that behavioural tests in social isolation may not accurately predict the environmental risk of chemical pollutants for group-living species and highlight the potential for social context to mediate the effects of psychoactive pollutants in exposed wildlife.